(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2019)
Artificial neural networks usage, as a developed technique, increased in many fields such as Auditing business. Contemporary auditor should cope with the challenges of the technology evolution in the business environment by using computerized techniques such as Artificial neural networks, This research is the first work made in the field of modern techniques of the artificial neural networks in the field of auditing; it is made by using thesample of neural networks as a sample of the artificial multi-layer Back Propagation neural networks in the field of detecting fundamental mistakes of the financial statements when making auditing. The research objectives at offering a methodology for the application of theartificial neural networks within professional practices, and showing its role in supporting thedecision making at the planning stage of the auditing processes and in detecting the fundamental errors as it is a supporting technique to show the technical opinion of the auditor. the most important of them are Artificial neural networks helps the auditor to use modern artificial intelligence in detecting and determining fundamental errors, and their impact on the consequent decisions made in the planning stage of the auditing process and in supporting the technical opinion of the auditor, and recommendations are made to use readymade automatic systems for the auditing business that is better made if using the advanced artificial intelligence techniques that make it possible to schedule the business, planning for the work, following up the implementation, supporting the professional opinion of the auditor.